Rocketship and the Rural Health Workforce Revolution in the Pacific: Growing Skilled Medical Generalists Across the "Blue Continent" - Lachlan McIver; Dan Manahan; Sam Jones; Lisiate 'Ulufonua; Lisiate 'Ulufonua (Frontiers Media S.A., 2021)
Dramatic shifts are occurring in the size, shape and skill of rural health workforces in Pacific island countries (PICs) due to an unprecedented convergence of political agreement, policy commitment, donor support and technical assistance. In particular, the impact of "medical internationalism" is being felt across the Pacific region, with new doctors returning home in far greater numbers than ever before, the majority having graduated from medical schools in Cuba, China and other countries outside the region, in addition to the more typical numbers graduating and returning home from the region's main medical schools in Fiji and Papua New Guinea. With an agreed regional vision of "Healthy Islands" across the Pacific, the main objective of expanding overseas training opportunities for Pacific island medical students has been to correct the widespread centralization and maldistribution of the medical workforce in PICs and improve health access and quality of care in rural areas by deploying the new graduates to outer-island facilities. However, the return of these new graduates in several PICs has demonstrated that additional training is required to equip them with the knowledge and skills necessary to practice safely and sustainably in unsupervised settings. Thus, the development of specific postgraduate programmes has been urgently needed to provide pathways to vocational training and specialization in rural medicine appropriate to the Pacific region. Rocketship Pacific Ltd. (Rocketship) is an international health charity, based in Australia, dedicated to improving health in Pacific island countries through stronger primary care. Rocketship's particular focus to date has been on education and capacity-building for doctors and nurses working in rural communities and outer-island facilities. Since 2015, Rocketship has been working in partnership with the Ministries of Health and other key partners in Solomon Islands, Timor-Leste, Tonga and Vanuatu to design and deliver postgraduate training programmes in the core generalist disciplines family, community and rural hospital medicine. To date, this has resulted in new postgraduate Family Medicine courses being established in Timor-Leste and Tonga; a rural medical workforce support programme being delivered in Vanuatu; and a new Postgraduate Diploma in Rural Generalist Medicine being designed in Solomon Islands. These new programmes, as well as other notable initiatives elsewhere in the Pacific such as the Master of Medicine (Rural) programme in Papua New Guinea, the Diploma and Master of Family Medicine programme in Fiji and the Cook Islands Fellowship in General Practice, are transforming the health workforce in PICs with the potential to benefit island people across the "Blue Continent." This paper describes the establishment of new postgraduate training programmes in family, community and rural hospital medicine in Timor-Leste, Tonga, Solomon Islands and Vanuatu from the perspective of Rocketship, the non-profit organization engaged by each country's Ministry of Health (or equivalent) to provide expert technical assistance with their initiative.